Effect of Tamoxifen Treatment on Lipid Profile in Hormone Receptor Positive Breast Cancer Women in Duhok City: A Cross-Sectional Study - Hussein, Darya Salih; Abduljabbar, Rezvan Faisal (Asian Pacific Journal of Cancer Care, 2025)
Objectives: Tamoxifen’s anti-estrogenic properties may have an impact on lipid metabolism; therefore, each patient’s risk-benefit profile must be carefully considered. This study examines how tamoxifen affects Kurdish women’s lipid profiles. Methods: The study is conducted on 120 females with (ER and /or PR) positive breast cancer on adjuvant hormonal therapy with tamoxifen (in a dose 20 mg once daily) for 3 months and more, at Azadi Hematology Oncology Center, Duhok city. Results: In this study, TG and VLDL-C are shown to increase with rising age and BMI. In contrast, all BMI categories show consistently reduced levels of HDL-C. Furthermore, TC levels were reduced but within the reference ranges in elder individuals, and the TC/HDL-C ratio rose with increasing BMI within the reference ranges. Conclusion: Healthcare professionals are encouraged to routinely check the lipid profiles of these patients and suggest lifestyle modifications. The long-term effects of tamoxifen on lipid metabolism, especially in larger populations, require more investigation.